Wireless water quality monitoring system for high density aquaculture application - F. A. Saparudin; T. C. Chee; A. S. Ab Ghafar; H. A. Majid; N. Katiran (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Water quality is one of the major factors that greatly affects growth and mortality rate of aquatic livestock especially in high density aquaculture system.  Conventional method requires fish farmer to perform manual water quality test and record on multiple fish tanks in regular basis. This process is meticulous, and may affect aquatic livestock that needs close and immediate attention. In this paper, water quality monitoring system for the high density aquaculture environment is proposed. The monitoring system is composed of multiple sensor nodes and sensor/server node hybrid, which used to collect and manage the water quality parameter data of multiple tanks. The sensor nodes collect and store the water quality parameters in local database and transmit them to the server node through a wireless communication. The server node is used for data analysis, processing and allow public access via web browser through various Wi-Fi enabled smart devices. This paper presents a proof-of concept of clustered wireless monitoring system focused on the use of multiple sensor nodes to determine the water parameter in real time. This system is cost effective, quickly deployable, and user-friendly with wireless capabilities.